Fasting plasma glucose and subsequent cardiovascular disease among young adults: Analysis of a nationwide epidemiological database. (February 2021) - Kaneko, Hidehiro; Itoh, Hidetaka; Kiriyama, Hiroyuki; Kamon, Tatsuya; Fujiu, Katsuhito; Morita, Kojiro; Michihata, Nobuaki; Jo, Taisuke; Takeda, Norifumi; Morita, Hiroyuki; Yasunaga, Hideo; Komuro, Issei
Abstract: Background and aims: Using a nationwide epidemiological database, we aimed to clarify the association of fasting plasma glucose (FPG) with subsequent cardiovascular disease (CVD) risk among young adults. Methods and results: Medical records of 1, 180, 062 young adults (20–49 years old) without a prior history of CVD and who were not taking antidiabetic medications were extracted from the Japan Medical Data Center. We categorized the study population into four groups: normal, FPG level<100 mg/dL (1, 007, 747 individuals), normal-high, FPG level of 100–109 mg/dL (126, 602 individuals), impaired fasting glucose (IFG), FPG level of 110–125 mg/dL (32, 451 individuals), and diabetes mellitus (DM), FPG level ≥126 mg/dL (13, 262 individuals). The mean age was 39.7 ± 6.9 years, and 57.0% of the study population were men. Mean follow-up period was 1201 ± 905 days on average. Multivariable Cox regression analysis showed that IFG (hazard ratio [HR]; 1.38) and DM (HR; 2.09) increased the risk of myocardial infarction. Normal-high (HR; 1.11), IFG (HR; 1.18), and DM (HR; 1.59) groups had an elevated angina pectoris risk. DM (HR; 1.31) increased the risk of stroke compared to normal FPG levels. Normal-high levels (HR; 1.10), IFG (HR; 1.22) and DM (HR; 1.58) elevated the risk of heart failure. DM (HR; 1.69) increased the risk of atrial fibrillation. Conclusions: Our analysis of a nationwide epidemiological database demonstrated a close association of the FPG category with subsequent CVD risk. Our results exemplify the importance of optimal FPG maintenance for the primary prevention of CVD in young adults. Graphical abstract: Image 1 Highlights: Clinical evidence on the association of fasting plasma glucose with cardiovascular disease (CVD) in young adults is scarce. We analyzed the relationship between fasting plasma glucose and incidence cardiovascular events. Fasting plasma glucose level was associated with elevated incidence of cardiovascular disease events. Risk of myocardial infarction, angina pectoris, and heart failure increased before the development of diabetes mellitus. Our results suggest the clinical significance of optimal glycemic control in young adults for primary CVD prevention.